ACHIEVING TRUE HAPPINESS: A STUDY OF MUHAMMAD HOSSEIN TABATABAI’S PHILOSOPHICAL-MYSTICAL THOUGHT - Zamzami, Mukhammad; Hosseinieskandian, Abdullah; Zuhri, Achmad Muhibin; Haidary, Abdullah Haq Al; Babaei, Ali (Islam Futura, 2023)
The question of what constitutes true happiness has been a core philosophical issue that has warranted multiple attempts in the attempt to provide a final answer, either from a purely religious or philosophical perspective. The issue of happiness is closely connected to the meaning of life and its ultimate outcome and purpose. The modern Muslim philosopher Muhammad Hossein Tabatabai discussed the nature of happiness at length. In his view, human beings instinctively strive to attain happiness or the ultimate good which can only be achieved through nearness to God. Therefore, true happiness requires the believer to commit righteous deeds and avoid sinful acts. This study follows a philosophical-Sufi approach and uses a descriptive-analytical method to examine the nature of happiness, the relationship between happiness, goodness and pleasure according to Tabatabai. In line with Islamic thought, true and lasting happiness can only be attained in the Hereafter, and happiness in this life, no matter how acutely and deeply felt, is merely a shadow of the true happiness of the believers who have attained God’s permission to enter Paradise.